PROVIDING QUALITY OF ELECTRIC POWER IN ELECTRIC POWER SYSTEM IN PARALLEL OPERATION WITH WIND TURBINE - Yu. A. Rolik; A. V. Gornostay (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
The problem of providing electric power quality in the electric power systems (EPS) that are equipped with sufficiently long air or cable transmission lines is under consideration. This problem proved to be of particular relevance to the EPS in which a source of electrical energy is the generator of wind turbines since the wind itself is an instable primary energy source. Determination of the degree of automation of voltage regulation in the EPS is reduced to the choice of methods and means of regulation of power quality parameters. The concept of a voltage loss and the causes of the latter are explained by the simplest power system that is presented by a single-line diagram. It is suggested to regulate voltage by means of changing parameters of the network with the use of the method of reducing loss of line voltage by reducing its reactance. The latter is achieved by longitudinal capacitive compensation of the inductive reactance of the line. The effect is illustrated by vector diagrams of currents and voltages in the equivalent circuits of transmission lines with and without the use of longitudinal capacitive compensation. The analysis of adduced formulas demonstrated that the use of this method of regulation is useful only in the systems of power supply with a relatively low power factor (cosφ < 0.7 to 0.9). This power factor is typical for the situation of inclusion the wind turbine with asynchronous generator in the network since the speed of wind is instable. The voltage regulation fulfilled with the aid of the proposed method will make it possible to provide the required quality of the consumers’ busbars voltage in this situation. In is turn, it will make possible to create the necessary conditions for the economical transmission of electric power with the lowest outlay of reactive power and the lowest outlay of active power losses.